A Place to Belong: Two Novels - A Cold Creek Homecoming and Coming Home to Crimson - Thayne, RaeAnne; Major, Michelle; Thayne, RaeAnne; Major, Michelle (Toronto, Ontario : Harlequin Selects, 2021)
A second chance at finding homeA Cold Creek Homecoming by New York Times bestselling author RaeAnne Thayne When Quinn Southerland discovers his foster moms hospice nurse is Tess Claybourne, hes surprised--and not in a good way! He still hasnt forgiven the former high school queen bee for how she treated him. But recently widowed Tess has learned a lot about life--and herself. And Quinn starts to wonder if he could be wrong about her. Is there room in his damaged heart for forgiveness...or love? FREE BONUS STORY INCLUDED IN THIS VOLUME!Coming Home to Crimson by Michelle Major Escaping from a cheating fianc ǐn a "borrowed" car, Sienna Pierce cant think of anywhere to go but Crimson, the hometown she swore shed never go back to. And Crimson sheriff Cole Bennett has a lot at stake in keeping the town on an even keel. On the surface, they have nothing in common. But theres nothing superficial about their feelings for each other!
"Previously published as A Cold Creek homecoming and Coming home to Crimson."
"Signature select."
Keywords: Man-woman relationships -- Fiction; Ranchers -- Fiction; Nurses -- Fiction; Widows -- Fiction; Downloadable electronic books; Electronic books; Romance fiction; Novels